Co-Designing Inclusive Interfaces: Participatory Approaches to Accessible E-Learning for Learners with Disabilities - Dewi, Ratna Kusuma; Sitorus, Anwar T (Digitus : Journal of Computer Science Applications, 2025)
Inclusive e-learning environments are essential for equitable access to education, especially for the over one billion people worldwide living with disabilities. However, many e-learning platforms fail to meet accessibility standards due to top-down, non-participatory design approaches. This study aims to evaluate how iterative participatory design methods, including low- and high-fidelity prototyping, impact the accessibility and usability of specific UI elements such as navigation, readability, and input modalities for learners with visual, motor, and cognitive disabilities. The research utilized an iterative participatory design framework involving 15 participants with diverse disabilities (visual, motor, cognitive). Through three stages—needs identification, low-fidelity prototyping, and high-fidelity UI development—users co-designed and evaluated inclusive UI features. Usability was measured through System Usability Scale (SUS) scores, task success rates, completion times, and qualitative interviews. Quantitative results showed a 37% increase in task success rate, a 45% reduction in error count, and an increase in SUS score from 61 to 84. Preferred features included keyboard navigation (93%), font size adjustment (87%), and high contrast modes (82%). Qualitative feedback highlighted the importance of layout consistency, minimal visual clutter, and labeled icons. The study found that participatory design yielded more functional and satisfying UIs than conventional methods and aligned well with accessibility standards like WCAG, UDL, and COGA, while also revealing their practical limitations. Participatory UI design significantly enhances the accessibility and usability of e-learning platforms. Involving users with disabilities as co-creators ensures better alignment with real needs and reinforces the ethical imperative of inclusive education. The findings support institutional adoption of participatory methods to create more equitable digital learning environments